Investigation of microbial flora of pigment gallstones on the basis of 16S ribosomal RNA gene analysis - A. K. Larin; P. L. Scherbakov; L. A. Kharitonova; O. A. Tsarkova; K. T. Momynaliyev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Investigation of microbial flora of pigment gallstones by analysis of ribosomal 16S RNA gene.Material and methods. Seven samples of pigment gallstones were obtained at cholecystectomy from children infected by H. pylori. DNA amplification method (PCR) was used for identification of microorganisms. Ligation, E. coli transformation and creation of clonal libraries were carried out. Nucleotide sequence was determined. Computer analysis of the obtained information was done; belonging of the read nucleotide sequences to certain microorganism by NCBI database was accomplished.Results. In 4 samples of black pigment stones no bacterial DNA was revealed. In 3 samples of brown pigment stones libraries of 16S rRNA gene fragments were created, their sequences were determined and microorganisms to which they belong were identified.Conclusion. At children infected by H. pylori, this microbe is not the cause of gallstones development.